Comments on "A decision feedback recurrent neural equalizer as an infinite impulse response filter" - Hacio?lu, Kadri (My University, 2000)
This correspondence corrects and clarifies some notation inconsistencies and the absence of some definitions in a previous paper by Ong et al.. In addition, we show that the assumptions made in the derivation of the MSEDFRNEMSERNE invalidate the final result given in Ong et al.and lead to an unfair comparison between the two equalizers. We present a simulation that best compares the two equalizers. © 2000 IEEE.
Keywords: Neural equalizers; Nonlinear equalization; Recurrent neural networks